2003
DOI: 10.1097/01.asn.0000073901.94759.36
|View full text |Cite
|
Sign up to set email alerts
|

Association of the Multidrug Resistance-1 Gene Single-Nucleotide Polymorphisms with the Tacrolimus Dose Requirements in Renal Transplant Recipients

Abstract: Abstract. The immunosuppressive drug tacrolimus, whose pharmacokinetic characteristics display large interindividual variations, is a substrate for P-glycoprotein (P-gp), the product of the multidrug resistance-1 (MDR1) gene. Some of the single nucleotide polymorphisms (SNP) of MDR1 reported correlated with the in vivo activity of P-gp. Because P-gp is known to control tacrolimus intestinal absorption, it was postulated that these polymorphisms are associated with tacrolimus pharmacokinetic variations in renal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
181
1
4

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 264 publications
(196 citation statements)
references
References 27 publications
10
181
1
4
Order By: Relevance
“…The contribution of MDR1 genetic polymorphisms has also been extensively studied for the calcineurin inhibitors cyclosporine and tacrolimus, which show large interindividual differences in oral bioavailability. Though two studies in renal transplant patients found cyclosporine and tacrolimus dose requirement to be higher in individuals homozygous for the 3435T allele (44,45), two other studies investigating tacrolimus steady-state dose requirement found an opposite effect, with plasma levels being lower in the 3435CC group after 3, 6, and 12 months (46,47). A recent study investigating the effect of genetic polymorphisms in CYP3A4, CYP3A5, and MDR1 on the pharmacokinetics of cyclosporine and tacrolimus also found no evidence supporting a role for the MDR1 C3435T polymorphism in dose requirement of the two drugs, consistent with previous reports regarding cyclosporin A trough levels and MDR1 genotype (48,49).…”
Section: Impact Of Mdr1 Genetic Polymorphism On Drug Dispositionmentioning
confidence: 98%
See 1 more Smart Citation
“…The contribution of MDR1 genetic polymorphisms has also been extensively studied for the calcineurin inhibitors cyclosporine and tacrolimus, which show large interindividual differences in oral bioavailability. Though two studies in renal transplant patients found cyclosporine and tacrolimus dose requirement to be higher in individuals homozygous for the 3435T allele (44,45), two other studies investigating tacrolimus steady-state dose requirement found an opposite effect, with plasma levels being lower in the 3435CC group after 3, 6, and 12 months (46,47). A recent study investigating the effect of genetic polymorphisms in CYP3A4, CYP3A5, and MDR1 on the pharmacokinetics of cyclosporine and tacrolimus also found no evidence supporting a role for the MDR1 C3435T polymorphism in dose requirement of the two drugs, consistent with previous reports regarding cyclosporin A trough levels and MDR1 genotype (48,49).…”
Section: Impact Of Mdr1 Genetic Polymorphism On Drug Dispositionmentioning
confidence: 98%
“…No difference in cyclosporine and tacrolimus dose requirement [49] Renal transplant patients T-129C, C1236T, G2677T/A (Ala893Ser/Thr), C3435T Tacrolimus Higher tacrolimus dose requirement in carriers of the 2677T/A alleles [44] Pediatric heart transplant patients G2677T/A (Ala893Ser/Thr), C3435T Tacrolimus Higher tacrolimus blood levels at 6 and 12 months [47] Japanese women T-129C -Increased placental P-glycoprotein expression levels [22] Caucasian volunteers C1236T + G2677T/A (Ala893Ser/Thr) + C3435T…”
Section: Impact Of Mdr1 Genetic Variation On Expression and Function mentioning
confidence: 99%
“…3,4 As regards the MDR1 gene, we analyzed a 2677GϾT,A substitution in exon 21 and a 1236CϾT substitution in exon 12, both of which other studies have shown to significantly contribute to altered concentrations of immunosuppressants. 5 …”
Section: P Harmacogenetics Applies Information Relatedmentioning
confidence: 99%
“…[5,6]. ABCA1, le transporteur responsable de l'efflux du cholestérol entérocytaire au pôle basolatéral, n'est pas impliqué dans l'absorption intestinale du cholestérol [7][8][9]. De même, l'absorption intestinale du cholestérol n'est pas altérée chez des souris dépourvues de SRBI (scavenger receptor class B, type I), alors qu'in vitro, l'action de ce récepteur sélectif pour les esters …”
Section: Nouvelleunclassified
“…En cancérologie, le dépistage de la maladie de Gilbert (déficit partiel en glucuroconjugaison) est effectué lorsque l'on envisage un traitement par l'irinotécan 1 pour éviter des toxicités hématologiques ou digestives très graves [7]. Le développement de la pharmacogé-nétique intéresse directement d'autres classes thérapeutiques, par exemple les anticoagulants, les immunosuppresseurs ou les anti-protéases [8][9][10].…”
unclassified